The novel role of Kallistatin in linking metabolic syndromes and cognitive memory deterioration by inducing amyloid-β plaques accumulation and tau protein hyperphosphorylation - Weiwei Qi; Yanlan Long; Ziming Li; Zhen Zhao; Jinhui Shi; Wanting Xie; Laijian Wang; Yandan Tan; Ti Zhou; Minting Liang; Ping Jiang; Bin Jiang; et al. (eLife)
Accumulation of amyloid-β (Aβ) peptides and hyperphosphorylated tau proteins in the hippocampus triggers cognitive memory decline in Alzheimer’s disease (AD). The incidence and mortality of sporadic AD were tightly associated with diabetes and hyperlipidemia, while the exact linked molecular mechanism is uncertain. Here, the present investigation identified significantly elevated serum Kallistatin levels in AD patients concomitant with hyperglycemia and hypertriglyceridemia, suggesting potential crosstalk between neuroendocrine regulation and metabolic dysregulation in AD pathophysiology. In addition, the constructed Kallistatin-transgenic (KAL-TG) mice defined its cognitive memory impairment phenotype and lower long-term potentiation in hippocampal CA1 neurons accompanied by increased Aβ deposition and tau phosphorylation. Mechanistically, Kallistatin could directly bind to the Notch1 receptor and thereby upregulate BACE1 expression by inhibiting PPARγ signaling, resulting in Aβ cleavage and production. Besides, Kallistatin could promote the phosphorylation of tau by activating GSK-3β. Fenofibrate, a hypolipidemic drug, could alleviate cognitive memory impairment by downregulating Aβ and tau phosphorylation of KAL-TG mice. Collectively, the experiments clarified a novel mechanism for Aβ accumulation and tau protein hyperphosphorylation regulation by Kallistatin, which might play a crucial role in linking metabolic syndromes and cognitive memory deterioration, and suggested that fenofibrate might have the potential for treating metabolism-related AD.